Differential leucocyte detection by flow cytometry improves the diagnosis of genital tract inflammation and identifies macrophages as proinflammatory cytokine‐producing cells in human semen. (8th November 2013) - Fathy, A.; Chen, S. J.; Novak, N.; Schuppe, H.‐C.; Haidl, G.; Allam, J.‐P.
Summary Genital tract inflammation is considered as a major cause of male infertility with leucocytospermia as widely used diagnostic marker. However, threshold of 106 leucocytes ml−1 recommended by the WHO is a matter of debate. Moreover, leucocyte subpopulations and their impact cannot be identified by the routine peroxidase method (POM). Ejaculates of subfertile men (n = 47) were analysed by flow cytometry (FACS) using a bead‐based method. Leucocytes were identified by CD18 and further divided into macrophages (HLA‐Dr+/CD66abce‐) and neutrophils (HLA‐Dr‐/CD66abce+). IL‐1β, TNF‐α and IL‐6 production was investigated in these subpopulations. It was found that CD18‐positive cells correlated significantly with POM. However, only in samples with POM below 106 per millilitre, FACS detected significantly higher leucocyte numbers. Moreover, in 31% of these samples, FACS leucocyte detection reached threshold values greater than 1 × 106 ml−1, fulfilling the criteria for diagnosis of leucocytospermia. Neutrophils were the predominating leucocyte population. Nevertheless, in 24% of samples, macrophages encountered more than 50% of leucocytes. Most interestingly, only macrophages produced significant amounts of IL‐1β, TNF‐α and IL‐6. It is concluded that FACS improves detection and functional differentiation of seminal leucocytes as one of the diagnostic hallmarks of male genital tract inflammation.